Numerical analysis of the effects of wrinkles in the radius of curvature of L-shaped CFRP specimens on unfolding failure. (1st November 2022) - Journoud, P.; Bouvet, C.; Castanié, B.; Ratsifandrihana, L.
Abstract: Complex composite parts, and especially curved laminated composites, are more subject to defects than flat laminates. One of the most common defects is the presence of wrinkles, which can occur in the radius of curvature. Wrinkle effects must be studied to evaluate their influence on the mechanical properties of laminated composites. In this study, a numerical model was developed to take wrinkle and local delamination defects into consideration and assess their impact on the failure load of L-angle specimens under four-point bending tests. Experimental wrinkles based on a previous work were modelled using the Discrete Ply Model strategy and four-point bending simulations were run. The numerical model allowed the effects of each defect (local delamination and wrinkle) to be distinguished and their combined influence on the failure load to be studied with respect to the maximum misalignment.